2016
DOI: 10.18632/oncotarget.13159
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 enhances the anti-tumor activity of trastuzumab against breast cancer cells but causes fatal side effects in humanized tumor mice (HTM)

Abstract: Cancer immunotherapy has been shown to enhance established treatment regimens. We evaluated the potential reinforcing effect of IL-15 in trastuzumab treated humanized tumor mice (HTM) which were generated by concurrent transplantation of neonatal NOD-scid IL2Rγnull mice with human hematopoietic stem cells (HSC) and HER2 positive breast cancer cells (metastasizing SK-BR-3, solid tumor forming BT474).We found that trastuzumab treatment efficacy mainly depends on the immediate anti-tumorigenic cellular effect whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Another study confirmed that chronic exposure of IL-15 induces transformation of large granular lymphocyte leukemia in vitro (76). A recent paper reported that IL-15 caused fetal side effects when administered in mice bearing humanized tumors (77). In nonhuman primates, IL-15 was known to cause considerable dose-dependent toxicity such as grade 3/4 transient neutropenia, weight loss and skin rash at higher doses (78).…”
Section: Il-15 Superagonist Toxicitymentioning
confidence: 99%
“…Another study confirmed that chronic exposure of IL-15 induces transformation of large granular lymphocyte leukemia in vitro (76). A recent paper reported that IL-15 caused fetal side effects when administered in mice bearing humanized tumors (77). In nonhuman primates, IL-15 was known to cause considerable dose-dependent toxicity such as grade 3/4 transient neutropenia, weight loss and skin rash at higher doses (78).…”
Section: Il-15 Superagonist Toxicitymentioning
confidence: 99%
“…IL-15 is an essential cytokine for human NK cell homeostasis; nonetheless, early clinical assays including systemic IL-15 were withdrawn due to concurrent adverse events and dose-limiting toxicities ( 181 ). Similarly, IL-15 enhanced the antitumor activity of trastuzumab, yet causing fatal side effects in a humanized tumor mice model ( 182 ). Current research efforts include the development of cytokine variants with extended in vivo half-life and targeted action on precise lymphocyte subsets and tumor sites (i.e., engineered IL-2 “superkine,” IL-15Rα Sushi-Fc fusion protein; IL-15 tri and tetraspecific killer engagers) ( 183 186 ).…”
Section: Enhancing Nk Cell-mediated Adcc Through Immunotherapy In Hermentioning
confidence: 99%
“…More specifically, the CD4/CD8 T-cell ratio was significantly increased by the administration of B100 to HTM. We previously described a preferred CD4 T cell activation over an activation of cytotoxic T cells in HTM both without [19] and with antibody (trastuzumab) treatment [20]. Thus, a cytotoxic CD4 cell activity triggered by the application of therapeutic antibodies seems to play a relevant role in HTM.…”
Section: Discussionmentioning
confidence: 98%
“…Tissue specimens (tumor, spleen, liver, brain, and lung) were prepared as previously described [19,20]. Briefly, samples were fixed with 4% formalin and embedded in paraffin.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation